The Last Hurrah (and The Long Haul): co-creation of theatre as climate change education. Issue 4 (2nd October 2021) - Law, Matt; Corbin, Siôbhan; Wilkins, Matt; Harris, Victoria; Martin, Georgia; Lowe, Rew
ABSTRACT: Meaningful action on climate change requires affective engagement with the human impacts of the problem. The Last Hurrah (and The Long Haul) project was developed using theatrical storytelling as a tool to provoke thought and empathy about the lived experience of climate change. Over a period of 3 years, a company of Acting students and their lecturer worked with faculty and students from a Geography department to explore climate change stories and the physical and human geographies that shape their impacts. This paper reflects on the process, highlighting opportunities and challenges for Geographers to become involved in interdisciplinary teaching and creative engagement as part of a more holistic approach to wicked problems, and explores the impact of the learning experience with the students involved. We conclude that storytelling is profoundly suited to overcoming the psychological barriers that can stand in the way of appreciating and empathizing with the implications for everyday life of an altered climate system. Recommendations are made for future interdisciplinary education projects using creative arts to address global challenges.